Inequality criteria for existence of solutions to some fractional partial differential equations. (March 2020) - Odzijewicz, Tatiana
Abstract: This paper deals with two types of fractional partial differential equations. By using some facts on ordinary fractional differential equations, we prove the Lyapunov-type and the De La Vallée Poussin-type inequalities for considered problems. We illustrate our results through several examples.